2014
DOI: 10.1063/1.4870762
|View full text |Cite
|
Sign up to set email alerts
|

Site-dependent charge transfer at the Pt(111)-ZnPc interface and the effect of iodine

Abstract: The electronic structure of ZnPc, from sub-monolayers to thick films, on bare and iodated Pt (111) is studied by means of X-ray photoelectron spectroscopy (XPS), X-ray absorption spectroscopy (XAS) and scanning tunneling microscopy (STM). Our results suggest that at low coverage ZnPc lies almost parallel to the Pt(111) substrate, in a non-planar configuration induced by Zn-Pt attraction, leading to an inhomogeneous charge distribution within the molecule and charge transfer to the molecule. ZnPc does not form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 81 publications
(143 reference statements)
1
17
0
Order By: Relevance
“…In the case of 3 ML coverage, there is also a pronounced shoulder attributed to the relative shakeup satellites, which locate at 1.9 eV higher binding energy compared to the main peaks and are well consistent with other reports of metal phthalocyanine. 23,44,55 Secondly, the peak shape was preserved well for all spectra during annealing either at monolayer or multilayer. Similar to the case of N 1s spectra, there is a peak shi of 0.4 eV when annealed at 673 K for monolayer and less than 0.1 eV for multilayer with respect to the spectrum as deposited at RT, which again shall be attributed to the polarization screening effect from metal substrate due to desorption of macrocycle induced by thermal annealing.…”
Section: Resultsmentioning
confidence: 82%
“…In the case of 3 ML coverage, there is also a pronounced shoulder attributed to the relative shakeup satellites, which locate at 1.9 eV higher binding energy compared to the main peaks and are well consistent with other reports of metal phthalocyanine. 23,44,55 Secondly, the peak shape was preserved well for all spectra during annealing either at monolayer or multilayer. Similar to the case of N 1s spectra, there is a peak shi of 0.4 eV when annealed at 673 K for monolayer and less than 0.1 eV for multilayer with respect to the spectrum as deposited at RT, which again shall be attributed to the polarization screening effect from metal substrate due to desorption of macrocycle induced by thermal annealing.…”
Section: Resultsmentioning
confidence: 82%
“…16,35,45 This is at variance with previous findings for TbPc 2 or phthalocyanine molecules in direct contact with a bulk TiO 2 substrate where oxidation of the molecular species was observed. [31][32][33][34][35] Such difference in the substrate reactivity could be an indication of the absence of catalytic sites characteristic of many TiO 2 surfaces, such as oxygen vacancies, 30,31 or it can be attributed to a different intrinsic reactivity of the TiO 2 lepidocrocite structure compared to the rutile phase used in our previous investigation. 35,46 We notice that also the Ti2p and O1s spectra collected after the TbPc 2 deposition (Figure 1a and Figure S1, bottom panels) do not reveal significant variations in both the line shape and the semiquantitative analysis (Table S1), thus confirming the innocent role played by the TiO 2 layer on the assembled molecules.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 In particular, the deposition of metallated phthalocyanines (MPc) systems on a bulk TiO 2 substrate showed that molecules in direct contact with the surface interact strongly and can undergo an oxidation process. [31][32][33][34] Furthermore, our recent studies on bulk TiO 2 single crystals revealed that also the sub-monolayer of TbPc 2 molecules deposited on the TiO 2 (110) rutile surface undergo a strong interfacial interaction independently on the surface preparation and the presence of surface defects. 35 In this work, we studied the molecular organization and the magnetic properties of a sub-monolayer of TbPc 2 molecules thermally sublimated on a TiO 2 film grown with a lepidocrocite-like structure on Ag(100) (TiO 2 -L).…”
Section: Introductionmentioning
confidence: 99%
“…MPc-s are planar organometallic molecules containing eight N atoms: four aza nitrogens (N–, marked in blue in Figure a), and four iminic nitrogens coordinated to the metal core (metal–N, in red in Figure a). Despite their nonequivalence, it is well-known that the 1s core levels of the two types of N atoms lie very close in energy (e.g., ∼ 0.3 eV for CuPc), which normally leads to the observation of an unresolved single N 1s core level peak in photoemission experiments. , However, unexpected features are frequently found in the N 1s energy region. This is the case, for example, of some MPc molecules deposited on Cu(110).…”
mentioning
confidence: 99%
“…Despite their nonequivalence, it is well-known that the 1s core levels of the two types of N atoms lie very close in energy (e.g., ∼ 0.3 eV for CuPc 30 ), which normally leads to the observation of an unresolved single N 1s core level peak in photoemission experiments. 31,32 However, unexpected features are frequently found in the N 1s energy region. This is the case, for example, of some MPc molecules deposited on Cu(110).…”
mentioning
confidence: 99%